Design and construct multiple linear facets integrated collector storage solar water heater (ICSSWH) - Fon, Chun Yin (2018)
Solar energy is a free, clean and safe form of energy source which can be obtained repetitively and persistently from the natural environment. The solar energy can be harvested and converted into thermal energy by solar water heater for domestic usage. Solar water heater is a well-established technology for water heating in many countries around the world. There are many different solar water heater systems and solar collectors available in the market due to the needs of different locations and applications. However, there are some weaknesses for all these solar water heater systems and solar collectors. In this project, a simple, high efficiency and easy fabricated multiple linear facets integrated collector storage solar water heater (ICSSWH) is constructed. A totally new design solar collector, multiple linear facets collector is designed by using trigonometry approach and ray tracing simulation is carried out to validate the design. Besides that, the mechanical structure of multiple linear facets ICSSWH is designed by using SolidWorks and then constructed in UTAR. The experimental study and cost analysis of the multiple linear facets ICSSWH are carried out and presented in detailed in this project. Lastly, the multiple linear facets ICSSWH has proved that it can achieved the theoretical maximum efficiency of 65.27% and highest water temperature of 83.0C with a payback period of 4.23 years.